The Quality of Science Literacy Instruments on Harmonic Vibration Material: Integration of Baayun Maulid Local Wisdom with Pancasila Student Profiles - Dewi Dewantara; Mustika Wati; Nadia Rezka Maulida; Sri Hartini; Surya Haryandi (Universitas Pendidikan Mandalika, 2026)
This study aims to describe the quality of a scientific literacy instrument on harmonic oscillation topics that integrates Baayun Maulid local wisdom and the Pancasila Student Profile. The research employed a Research and Development (R&D) design based on the Sugiyono model. In the development stage, design validity was obtained with very good results. A pilot study involving 20 items was conducted, and 12 items met the criteria of validity, reliability, difficulty level, and discrimination power, while the rest were revised or discarded. These 12 items were then used in the large-scale trial (field testing). The trial, conducted in the eighth stage of development, involved 97 students from three senior high schools in Banjarmasin. The analysis showed that 10 of the 12 items fulfilled the required psychometric criteria, while 2 items did not and were eliminated. The findings indicate that the instrument meets the standards of a quality evaluation tool. The implication of this study is the availability of a relevant instrument to assess scientific literacy while embedding local cultural values and character education aligned with the Pancasila Student Profile. This instrument provides an alternative for contextual science assessment and contributes to the development of evaluation practices consistent with national minimum competency assessment standards.